Implementasi Pembelajaran Berbasis Bermain melalui Engagement Belajar Anak Usia Dini - Sehati, Rindu; Pohan, Selamat (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Low early childhood learning engagement in Indonesia poses a serious challenge in national education quality development. Based on the data of the Ministry of Education, Culture, Research, and Technology in 2023, as many as 47% of early childhood children show low learning interest, which is rooted in learning approaches that do not match the child’s characteristics. This study aims to explore strategies for improving learning engagement through strengthening teachers’ competencies in the application of play-based learning. The research method used was a descriptive qualitative approach, with data collection techniques through observation and documentation in early childhood institutions. Data analysis was conducted with the Miles, Huberman, and Saldana model through the process of reduction, presentation, and drawing conclusions. Study results show that play-based learning has positive implications on increasing motivation, active participation, as well as holistic child cognitive, social-emotional, language, and motor development. However, the effectiveness of this approach is highly dependent on teachers’ competence in designing, managing, and evaluating educational, structured play activities. Findings also affirm that enhancing teacher professionalism, through training, accompaniment, and reflective collaboration, is a major key in optimizing the implementation of play-based learning. This study recommends the importance of integrating a playful approach in the early childhood curriculum and strengthening teachers’ pedagogical capacities as a strategic effort in building a foundation of participatory, inclusive, and child development-oriented education from an early age.